Arthroscopic Resection of Infrapatellar Fat Pad Impingement Syndrome: Long-Term Clinical Results at Minimum 10-Year Follow-Up - Young-Cheol Park; Young-Mo Kim; Yong-Bum Joo (Medicina, 2025)
Background and Objectives: Infrapatellar fat pad impingement syndrome (IFPIS) is a relatively underdiagnosed cause of anterior knee pain. While conservative management is the initial approach, some patients require surgical intervention. This study aimed to evaluate the long-term clinical and radiologic outcomes following arthroscopic resection of the infrapatellar fat pad in patients with IFPIS. Materials and Methods: Eighteen patients (10 females, 8 males; median age 22) diagnosed with IFPIS and unresponsive to conservative therapy underwent arthroscopic partial or subtotal resection between 2007 and 2013. Diagnosis was based on physical examination (Hoffa’s test), MRI findings, and response to lidocaine injection. Clinical outcomes (VAS, IKDC-2000, Kujala, Lysholm, Tegner activity scores) and radiologic assessments (ISR, CDI, PFJ osteoarthritis grade) were evaluated preoperatively, at 2 years, and at a final follow-up (mean 148.7 months). Results: All clinical scores significantly improved postoperatively. VAS decreased from 7.25 ± 0.79 to 2.43 ± 1.50 at 2 years, and to 3.66 ± 1.50 at the final follow-up (p < 0.001). Similar long-term improvements were observed in the Kujala, IKDC-2000, Lysholm, and Tegner scores (all p < 0.001). Radiographic parameters including ISR and CDI remained stable, and there was no statistically significant progression in patellofemoral osteoarthritis. However, 5 of 18 patients (27.8%) reported persistent symptoms at long-term follow-up. Conclusions: Arthroscopic resection of the infrapatellar fat pad in patients with IFPIS showed favorable and sustained clinical outcomes over a 10-year follow-up, without significant radiological changes. These results suggest that arthroscopic resection is a viable treatment option when accurate diagnosis is established.